Cost-Effectiveness of Interventions to Improve HIV Pre-exposure Prophylaxis Initiation, Adherence, and Persistence Among Men Who Have Sex With Men. (1st May 2022) - Wheatley, Margo M.; Knowlton, Gregory; Kao, Szu-Yu; Jenness, Samuel M.; Enns, Eva A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: To help achieve Ending the HIV Epidemic (EHE) goals of reducing new HIV incidence, pre-exposure prophylaxis (PrEP) use and engagement must increase despite multidimensional barriers to scale-up and limitations in funding. We investigated the cost-effectiveness of interventions spanning the PrEP continuum of care. Setting: Men who have sex with men in Atlanta, GA, a focal jurisdiction for the EHE plan. Methods: Using a network-based HIV transmission model, we simulated lifetime costs, quality-adjusted life years (QALYs), and infections averted for 8 intervention strategies using a health sector perspective. Strategies included a status quo (no interventions), 3 distinct interventions (targeting PrEP initiation, adherence, or persistence), and all possible intervention combinations. Cost-effectiveness was evaluated incrementally using a $100, 000/QALY gained threshold. We performed sensitivity analyses on PrEP costs, intervention costs, and intervention coverage. Results: Strategies averted 0.2%–4.2% new infections and gained 0.0045%–0.24% QALYs compared with the status quo. Initiation strategies achieved 20%–23% PrEP coverage (up from 15% with no interventions) and moderate clinical benefits at a high cost, while adherence strategies were relatively low cost and low benefit. Under our assumptions, the adherence and initiation combination strategy was cost-effective ($86, 927/QALY gained). Sensitivity analyses showed no strategies were cost-effective when intervention costs increased by 60% and the strategy combining all 3 interventions was cost-effective when PrEP costs decreased to $1000/month. Conclusion: PrEP initiation interventions achieved moderate public health gains and could be cost-effective. However, substantial financial resources would be needed to improve the PrEP care continuum toward meeting EHE goals.